Authenticity of the Mushaf Utsmani - Mustafiah Nu'man; Halimah Basri; Andi Miswar (TAFASIR: Journal of Quranic Studies, 2026)
This paper examines the authenticity of the mushaf utsmani by highlighting three main aspects: the historical process of the Uthmanic codification, the evidences supporting its authenticity, and the views of Orientalists along with the Muslim scholarly rebuttals concerning the Uthmanic mushaf. The background of this research stems from the increasing modern critiques of the Qur’an’s textual authenticity, which necessitate a comprehensive re-examination. This research employs a historical approach and Qur’anic sciences through a qualitative–descriptive library research method, critically analyzing primary and secondary sources related to the history of the Uthmanic codification process.. The findings indicate that the authenticity of the Uthmanic mushaf can be demonstrated by tracing the historical stages of codification from the time of the Prophet, Abu Bakr, and finally ‘Uthman. Its authenticity is further reinforced by three fundamental pillars: the consensus (ijmāʿ) of the Companions, the consistency of the Uthmanic script (rasm), and the mutawātir recitations transmitted directly from the Prophet. The discussion also includes the critiques of Orientalists and the Muslim scholarly responses that academically affirm the integrity and genuineness of the text. This study concludes that the Uthmanic mushaf possesses strong historical and methodological foundations, and therefore remains the authentic and authoritative reference of the Qur’an to this day.  Keywords:  Authenticity of the Mushaf Utsmani, History of Codification, Orientalist Critique